Human Resource Management Strategy: Integrating Psychological Perspectives through Qualitative Description and Literature Review - Hadjo, Diana Yanmiraty; Ibrahim, Muhdi B. Hi; Irawan, Andri; Noch, Muh Yamin; Mustajab, Duta (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study explores the integration of psychological perspectives into Human Resource Management (HRM) strategy, aiming to understand its implications for organizational effectiveness. Employing a qualitative research design, the study conducts a systematic literature review to analyze existing literature relevant to the research topic. Data collection involves comprehensive search strategies using keywords related to HRM strategy, psychological perspectives, and organizational performance. Thematic analysis is employed to identify recurring patterns and themes within the literature. The findings indicate that integrating psychological perspectives into HRM strategy enhances employee motivation, engagement, and organizational performance. Psychological theories such as Maslow's hierarchy of needs, Herzberg's two-factor theory, and self-determination theory offer valuable insights into understanding employee behavior and motivation. The study highlights the importance of addressing employees' diverse psychological needs for autonomy, recognition, and meaningful work to foster a positive work environment. Furthermore, it emphasizes the role of talent development, recognition programs, and supportive leadership in enhancing organizational performance and competitiveness. The study concludes that integrating psychological perspectives into HRM strategy holds promise for promoting organizational effectiveness and employee well-being.